The effects of alterations in dietary carbohydrate intake on the performance of high-intensity exercise in trained individuals - Pitsiladis, Y. P.; Maughan, R. J. (European Journal of Applied Physiology, 1999)
These results indicate that moderate changes in diet composition during training do not affect the performance of high-intensity exercise in trained individuals when the total energy intake is moderately high.